Evolution of Apparent Diffusion Coefficient and Fractional Anisotropy in the Cerebrum of Asphyxiated Newborns Treated with Hypothermia over the First Month of Life - Saskia Kwan; Elodie Boudes; Anouk Benseler; Guillaume Gilbert; Christine Saint-Martin; Michael Shevell; Pia Wintermark (Neural Plasticity)
The objective of this study was to assess the evolution of diffusion-weighted imaging (DWI) and diffusion-tensor imaging (DTI) over the first month of life in asphyxiated newborns treated with hypothermia and to compare it with that of healthy newborns. Asphyxiated newborns treated with hypothermia were enrolled prospectively; and the presence and extent of brain injury were scored on each MRI. Apparent diffusion coefficient (ADC) and fractional anisotropy (FA) values were measured in the basal ganglia, in the white matter and in the cortical grey matter. Sixty-one asphyxiated newborns treated with hypothermia had a total of 126 ADC and FA maps. Asphyxiated newborns developing brain injury eventually had significantly decreased ADC values on days 2-3 of life and decreased FA values around day 10 and 1 month of life compared with those not developing brain injury. Despite hypothermia treatment, asphyxiated newborns may develop brain injury that still can be detected with advanced neuroimaging techniques such as DWI and DTI as early as days 2-3 of life. A study of ADC and FA values over time may aid in the understanding of how brain injury develops in these newborns despite hypothermia treatment.